Exploring the influence of spirituality on students' well-being - Magula, Nokuzola Princess (Rhodes University, Faculty of Humanities, Department of Psychology, 2013)
This study was aimed at exploring the impact of spirituality on the well-being of students at Rhodes University in South Africa. The study was conducted within a qualitative research paradigm deploying an interpretive phenomenological analysis strategy for data analysis. The study involved a sample of four female Honours students who were all active Christians. The selected students were interviewed to elicit their experiences of spirituality and how this related to their everyday lives. The study used semi-structured interviews in order to get as much information as possible from the small sample of research participants. Data generated in this study was processed, presented and interpreted inductively and hermeneutically in order to identify emerging superordinate themes. This study found that spirituality was experienced as having a positive impact on well-being by all the four students. The study revealed that belief and faith in God amongst the students resulted in enhanced and positive experiences of hope, optimism and compassion which provided the students with a deeper sense of meaning of life and a source of direction in difficult times. The study further showed that participants experienced spirituality as a regulatory mechanism shaping their lifestyles and behaviours. Participants viewed their spirituality and religiosity as a source of social support helping them to cope with distressful situations. The findings of this study are consistent with the findings of previous studies done in the field of psychology and spirituality. The fact that this study has shown that spirituality and religion has a positive impact on student's well-being may mean that University administrators and psychologists may find the study interesting and valuable
Keywords: Sprituality; Well-being; Students; Christians; Rhodes University; College students -- Religious life -- South Africa -- Eastern Cape; Christian college students -- Religious life -- South Africa -- Eastern Cape; Universities and colleges -- Religion -- Research; Well-being -- Religious aspects; Spirituality -- Research